PEREMPUAN MENURUT SUDUT PANDANG AL-QUR’AN DAN KLAIM HADIS MISOGINIS - Niskaromah, Niskaromah (Bajang Institute, 2025)
Al- Qur'an as Raḥmatan li al-'Alamīn clearly states that men and women have the same position in terms of rights and obligations as well as personal potential. Hadith - as the second source of law which functions to explain and strengthen the laws established by the Qur'an - also provides the same view.The claim that there are misogynistic hadiths containing statements by the Prophet that give the impression of marginalizing women should not be understood based on the text alone because it will result in a contradiction with the basic principles established by the Koran and the Hadith itself. Some Hadiths are claimed to be misogynistic such as; Hadith about the creation of women from the rib bones of men, hadith about many women going to hell because of their lack of intelligence and religion, hadith about angels cursing wives who are reluctant to have relations with their husbands, and so on. These hadiths have a degree of authenticity, therefore these hadiths are not correct if only understood from their express meaning but must also be understood implicitly.This research will discuss the position of women according to the perspective of al-Qur’an and Hadith which is claimed to be misogynistic through the approach QS. al-Ḥujurāt [49]: 13 which carries egalitarian principles, where humans have the same values regardless of gender apart from the size of their piety. The research results show that al- Qur'an firmly provides basic principles to women regarding the origins of their creation, their rights fairly. Inheritance issues, husband and wife relations, husband's rights towards wife and vice versa. The Hadith claim of misogyny by gender activists is solely that the Hadith text is understood textually without looking at the general principles set out in al-Qur’an and Hadith (apart from those claimed to be misogynistic).